The influence of the temperature of a mixture of lead nitrate and sodium hydroxide solutions on the growth peculiarities of lead sulfide films - Amirbekova, G.S.; Tolepov, Zh.K.; Guseinov, N.; Kuanyshbekov, T. (Recent Contributions to Physics, 2024)
The present work is devoted to studying the effect of temperature on the formation of a submicron-sized particles of lead sulfide (PbS). Lead sulfide samples were obtained by chemical bath deposition method. 25 ml of an aqueous solution of lead nitrate Pb(NO3)2, 75 ml of sodium hydroxide NaOH and 50 ml of thiourea CH4N2S with molar concentrations of 0.18 M (1.52 g), 0.38 M (1.151 g) and 0.11 M (0.397 g), respectively, were used as reagents. In the process of obtaining samples, solutions of lead nitrate and sodium hydroxide were initially mixed at temperatures of 70°C and 100°C, then a thiourea solution was added to this mixture. It was found that temperature has an effect on the formation of PbS structures. It is shown that at a temperature of 100°C isolated particles are formed, whereas at a temperature of 70°C a film is formed. The morphology and elemental composition of the obtained lead sulfide (PbS) samples were studied by scanning electron microscopy (SEM) and the surface structure was studied using an atomic force microscope (AFM). As a result of the study of the morphology and texture of the surface of lead sulfide samples, the average size of isolated particles was determined, which is ~144 nm, and these particles also had a cubic shape with a smooth surface.